Surface lattice resonances in THz metamaterials - Tan, Thomas CaiWei (2021)
Diffraction of light in periodic structures is observed in a variety of systems including atoms, solid state crystals, plasmonic structures, metamaterials, and photonic crystals. In metamaterials, lattice diffraction appears across microwave to optical frequencies due to collective Rayleigh scattering of periodically arranged structures. Light waves diffracted by these periodic structures can be trapped along the metamaterial surface resulting in the excitation of surface lattice resonances, which are mediated by the structural eigenmodes of the metamaterial cavity. This has brought about fascinating opportunities such as lattice-induced transparency, strong nearfield confinement, and resonant field enhancement and line-narrowing of metamaterial structural resonances through lowering of radiative losses. In this review, we describe the mechanisms and implications of metamaterial-engineered surface lattice resonances and lattice-enhanced field confinement in terahertz metamaterials. These universal properties of surface lattice resonances in metamaterials have significant implications for the design of resonant metamaterials, including ultrasensitive sensors, lasers, and slow-light devices across the electromagnetic spectrum.